2022
DOI: 10.1108/lht-11-2020-0285
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge mapping of research data in China: a bibliometric study using visual analysis

Abstract: PurposeThis study aims to provide a systematic and complete knowledge map for use by researchers working in the field of research data. Additionally, the aim is to help them quickly understand the authors' collaboration characteristics, institutional collaboration characteristics, trending research topics, evolutionary trends and research frontiers of scholars from the perspective of library informatics.Design/methodology/approachThe authors adopt the bibliometric method, and with the help of bibliometric anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Regarding research trends, Wani and Ganaie (2024) conducted a bibliometric analysis and found the publication of gray literature, information produced outside of traditional publishing and distribution channels, has been increasing recently, with prominent sources like PLOS One and NeuroImage. Yan et al (2024) provide a systematic knowledge map for researchers in the field of research data management and found that collaboration between scholars and institutions is weak. Results also identified current hotspots, including data literacy education, research data sharing, data integration management, joint library cataloging and data research support services.…”
Section: Current Research Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding research trends, Wani and Ganaie (2024) conducted a bibliometric analysis and found the publication of gray literature, information produced outside of traditional publishing and distribution channels, has been increasing recently, with prominent sources like PLOS One and NeuroImage. Yan et al (2024) provide a systematic knowledge map for researchers in the field of research data management and found that collaboration between scholars and institutions is weak. Results also identified current hotspots, including data literacy education, research data sharing, data integration management, joint library cataloging and data research support services.…”
Section: Current Research Trendsmentioning
confidence: 99%
“…and NeuroImage. Yan et al (2024) provide a systematic knowledge map for researchers in the field of research data management and found that collaboration between scholars and institutions is weak. Results also identified current hotspots, including data literacy education, research data sharing, data integration management, joint library cataloging and data research support services.…”
mentioning
confidence: 99%
“…WOS is an influential professional and comprehensive scientific information service platform in the research community, which has been accepted by many scholars and personnel [45], contains more than 12,000 world-authoritative and high-impact scholarly journals in a variety of research fields, such as natural sciences, engineering, and technology, and is considered to be the most suitable database for bibliometric analysis. Therefore, this paper uses the core data set of WOS as the source data.…”
Section: Data Sourcesmentioning
confidence: 99%
“…Therefore, we can accurately obtain relevant fields when conducting a bibliometric study. This database is one of the most important sources of bibliometric information in China (Feng, 2022;Yan, et al, 2022;Yun, et al, 2022).…”
Section: Data Collectionmentioning
confidence: 99%